2022
DOI: 10.3389/fpsyg.2022.957551
|View full text |Cite
|
Sign up to set email alerts
|

An app-enhanced cognitive fitness training program for athletes: The rationale and validation protocol

Abstract: The core dimensions of cognitive fitness, such as attention and cognitive control, are emerging through a transdisciplinary expert consensus on what has been termed the Cognitive Fitness Framework (CF2). These dimensions represent key drivers of cognitive performance under pressure across many occupations, from first responders to sport, performing arts and the military. The constructs forming the building blocks of CF2 come from the RDoC framework, an initiative of the US National Institute of Mental Health (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Cognitive strategies, including goal setting and emotional and attentional control, have also been shown to positively impact psychological well-being in military personnel [22][23][24][25]. Although there is growing evidence on the benefit of training cognitive stress management skills in first responders and similar occupational cohorts [26][27][28][29][30], further research is required to inform best practice strategies on how to effectively implement and scale training within and across organizations. A major challenge in this context is that many workplace and training organizations deliver training as scheduled activities and in groups.…”
Section: Stress Management Training In the Workforcementioning
confidence: 99%
“…Cognitive strategies, including goal setting and emotional and attentional control, have also been shown to positively impact psychological well-being in military personnel [22][23][24][25]. Although there is growing evidence on the benefit of training cognitive stress management skills in first responders and similar occupational cohorts [26][27][28][29][30], further research is required to inform best practice strategies on how to effectively implement and scale training within and across organizations. A major challenge in this context is that many workplace and training organizations deliver training as scheduled activities and in groups.…”
Section: Stress Management Training In the Workforcementioning
confidence: 99%
“…Finally, in most cases, the associations between cognitive fitness traits and sleep and mental health did not differ between men and women athletes. As future research explores the utility of cognitive fitness training, our findings generate the hypothesis that the performance and mental health of men and women athletes would benefit from training programs targeting cognitive fitness ( Aidman et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…The ingredients of cognitive fitness studied here were drawn from a theory-driven model ( Aidman, 2020 ) which in turn is based on Research Domain Criteria ( Clark et al, 2017 ) and supported by a transdisciplinary Delphi study ( Albertella et al, 2023 ). The cognitive fitness framework suggests that cognitive fitness factors, although initially trait-based, can be trained for sustained optimal performance ( Aidman et al, 2022 ; Albertella et al, 2023 ). Women competitive athletes in the current study reported poorer cognitive fitness in multiple domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proliferation of smartphones and growing awareness of the significance of regular exercise and healthy living have contributed to the widespread adoption of fitness apps (Huang & Zhou, 2018). The apps have effectively catered to diverse users, ranging from fitness enthusiasts and athletes to beginners seeking guidance and motivation (Aidman et al, 2022;Molina & Myrick, 2021).The widespread adoption of fitness apps has been attributed to their ability to harness technology, offering innovative features and functionalities (Conroy et al, 2014). Such features empower users to set goals, track progress, and receive real-time feedback, fostering motivation and accountability (Muntaner-Mas et al, 2019).…”
mentioning
confidence: 99%